THE EFFECT OF EMOTIONAL INTELLECTUAL INTELLIGENCE, ADVERSITY AND LEARNING BEHAVIOR ON UNDERSTANDING OF FINANCIAL REPORTING CONCEPTS WITH ENVIRONMENTAL CONDITIONS AS A MODERATING VARIABLE (Empirical Study of Accounting Students in Lamongan Regency) - Arif, Rochman; Ghofur, Abdul; Syafik, Mohammad; Nurjanah, Fitri; Ibra Yudha Andrian Hakim (Proceeding of International Management Conference and Progressive Papers, 2025)
This study aims to analyze the influence of emotional intelligence, intellectual intelligence, Adversity quotient, and learning behavior on the understanding of financial statement concepts, with environmental conditions as a moderating variable. The research was conducted on accounting students in Lamongan Regency. Financial statements are a crucial element in accounting; therefore, a strong understanding of their concepts is essential for students as future accountants. This study employed a quantitative approach using primary data collected through questionnaires. The analytical techniques used were multiple linear regression and Moderated Regression Analysis (MRA). The results of the study show that intellectual intelligence and learning behavior have a significant positive effect on the understanding of financial statement concepts. Emotional intelligence and adversity do not have a significant effect, while the four variables moderated by environmental conditions do not show a significant effect. Simultaneously, the four variables, both with and without environmental conditions, contribute positively to improving the understanding of financial statement concepts. These findings highlight the importance of developing cognitive intelligence, effective learning behavior, and creating a conducive learning environment to enhance students’ understanding of accounting. Keywords: Emotional Intelligence, Intellectual Intelligence, Adversity Quotient, Learning Behavior, Understanding of Financial Statement Concepts, Environmental Conditions